2016
DOI: 10.1182/blood.v128.22.4024.4024
|View full text |Cite
|
Sign up to set email alerts
|

Blinatumomab + Tyrosine Kinase Inhibitors in the Treatment of Relapsed Philadelphia Chromosome Positive Acute Lymphoblastic Leukemia Patients - Clinical Efficacy and Peripheral Blood Lymphocytes Subpopulations Kinetics

Abstract: Blinatumomab is a bispecific anti-CD3/CD19 monoclonal antibody. It showed efficacy as a single agent in the treatment of relapsed/refractory Philadelphia chromosome positive acute lymphoblastic leukemia (Ph+ ALL). T-regulatory (T-reg) and T-helper cells can inhibit effector T-cells used by blinatumomab. Tyrosine-kinase inhibitors (TKI) are the basic treatment of the Ph+ ALL. To improve the long-term results of the relapsed Ph+ ALL treatment we combined blinatumomab with TKIs dasatinib or nilotinib or ponatinib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Their study examined the combinatorial treatment of ponatinib (anti-FGFR2 inhibitor) and ridaforoli-mus (anti-mTOR agent) and demonstrated the dual inhibition of both molecules in vitro and also induced tumor regression in an endometrial cancer model. Furthermore, Sokolov discovered that the combination of blinatumomab (a monoclonal antibody) and ponatinib resulted in improved long-term results in the treatment of relapsed Ph+ ALL 70. Based on these results, a Phase II clinical trial (NCT03263572) on this dual combination is currently recruiting Ph+ ALL patients 71…”
Section: Preclinical Evaluation Of Ponatinib In Other Tumor Typesmentioning
confidence: 99%
“…Their study examined the combinatorial treatment of ponatinib (anti-FGFR2 inhibitor) and ridaforoli-mus (anti-mTOR agent) and demonstrated the dual inhibition of both molecules in vitro and also induced tumor regression in an endometrial cancer model. Furthermore, Sokolov discovered that the combination of blinatumomab (a monoclonal antibody) and ponatinib resulted in improved long-term results in the treatment of relapsed Ph+ ALL 70. Based on these results, a Phase II clinical trial (NCT03263572) on this dual combination is currently recruiting Ph+ ALL patients 71…”
Section: Preclinical Evaluation Of Ponatinib In Other Tumor Typesmentioning
confidence: 99%
“…A retrospective study of 12 patients reported use of BLIN in combination with TKI resulting in CR of 50% and 1-year OS of 73% [67]. In another study of 6 patients where BLIN was used with a TKI (dasatinib, imatinib, ponatinib), 33% received HSCT while 50% were awaiting HSCT at the time of publication [68]. Given preliminary safety data and the possibility that combination therapy may maximize disease control, as an off-label use in clinical practice, BLIN is often combined with TKI in R/R Ph+ ALL.…”
Section: R/r Ph+ B-cell Allmentioning
confidence: 99%
“…Other subsequent retrospective studies including a total of 33 patients treated with blinatumomab plus a TKI further support these findings. 40,41 To prospectively confirm these findings, ongoing clinical trials are evaluating blinatumomab plus TKI combinations in patients with relapsed/refractory Ph-positive ALL, including blinatumomab + ponatinib (NCT03263572), and chemotherapy + blinatumomab + ponatinib (NCT03147612).…”
Section: Ph-positive B-cell Allmentioning
confidence: 96%